Effects of rooting media and varieties on rooting performance of dragon fruit cuttings (Hylocereu sundatus Haw.) - Rahad, MAB Khalil; Islam, M Ashraful; Rahim, M Abdur; Monira, S (Research in Agriculture Livestock and Fisheries, 2016)
The experiment was carried out to investigate the effects of different rooting media on rooting performance, plant growth and development of two varieties of Pitahaya (dragon fruit) cuttings at the Fruit Tree Improvement Project (FTIP), Germplasm Centre (GPC) of Bangladesh Agricultural University (BAU), Mymensingh during the period from May 2014 to August 2014. The two factors experiment consisted with of two different varieties of dragon fruit viz., BAU Dragon fruit-1 (V1) and BAU Dragon fruit-2 (V2) with 14 rooting media. viz. control (soil 100%) (T0), 50% cow dung + 50% soil (T1), Saw dust (100%) (T2), Compost (100%) (T3), 50% soil + 50% sand (T4), 50% soil + 50% saw dust (T5), Sand (100%) (T6), Indole-3 Acetic Acid (IAA) 500 ppm solution + soil (100%) (T7), 300 ppm solution + soil (100%) (T8), 200 ppm solution of IAA + soil (100%) (T9), 500 ppm solution of Indole-3 Butyric Acid (IBA) + soil (100%) (T10), 300 ppm solution IBA + soil (100%) (T11), 200 ppm solution IBA + soil (100%) (T12), (IBA+IAA) 200 ppm solution of each + soil (100%) (T13). All the parameter showed significant effect except number of branches per plant. In case of variety less time was needed for first root initiation (22.33 days) with the longest plant height (34.02 cm). The better result regarding number of roots per cutting (6.00) was found in case of BAU dragon fruit-2 (V2) where the highest root length (15.22 cm). In case of different treatment, the better result regarding number of roots per cutting (8.17) at 100 DAP was counted from the combination of (IAA+IBA) 200 ppm solution + soil (100%) (T13). The highest root length (25.38 cm) was observed in IAA 200 ppm solution + soil (100%) (T9). In case of combined effect, the minimum time was required for first root initiation (20.78 days) with IAA 300 ppm solution + soil (100%) (T8). The highest root length (25.87 cm) was observed in BAU Dragon fruit-1 with IAA 200 ppm solution + soil (100%) (V1T9). Number of roots per cutting was noticed (9.67) in BAU Dragon fruit-2 200 ppm solution of each IAA and IBA + soil (100%) (V2T13). Res. Agric., Livest. Fish.3(1): 67-77, April 2016